Strategi Pemasaran Agrowisata Kebun Buah Cipta Rasa di Kecamatan Sebangau Kota Palangka Raya - Hutapea, Rivaldo Hasiholanta; Yusuf, Syamsuri; Sunaryati, Revi; Asiaka, Fandi K.P.; Ahmad, (J-SEA (Journal Socio Economic Agricultural), 2026)
Agrotourism is part of the tourism sector with significant potential to stimulate regional economic growth. However, the high level of competition among tourism destinations in Palangka Raya City requires appropriate marketing strategies to enhance competitiveness and optimize market opportunities. This study aimed to analyze the internal and external factors influencing the marketing of Cipta Rasa Agrotourism and to formulate appropriate marketing strategies based on those factors. This research employed a SWOT analysis approach using internal and external factors identified through the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices. The results showed that the internal marketing factors of Cipta Rasa Agrotourism were in a strong position, with an IFE score of 3.03, while external factors indicated a favorable response to opportunities, with an EFE score of 2.91. The SWOT diagram positioned the agrotourism business in Quadrant I (aggressive strategy), indicating that growth-oriented strategies should be prioritized. Recommended S-O strategies include optimizing location and human resources, utilizing digital technology in marketing, and improving accessibility and supporting facilities. In conclusion, the appropriate marketing strategy for Cipta Rasa Agrotourism is an aggressive growth strategy that leverages internal strengths to capture external opportunities and improve destination competitiveness through sustainable innovation and service quality.